Orthographic Transparency, Literacy Development, and Language Maintenance in Hawu: Evidence from Eastern Indonesia - Thersia Magdalena Tamelan; Ifoni Ludji; Susi Ga Dara; Zuvyati A. Tlonaen (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Orthographic transparency plays an important role in literacy development and language maintenance, particularly in minority and endangered language communities. This study investigates the representation of implosive consonants and the mid-central vowel /?/ in three Hawu orthographic traditions: UBB GMIT, Lembaga Alkitab Indonesia (LAI), and Paddi. Using a qualitative descriptive approach, the study analyzes published orthographic materials supplemented by observations from 12 native Hawu speakers representing different age groups and educational backgrounds. The analysis examines phoneme–grapheme correspondences, orthographic transparency, and their implications for literacy development and language maintenance. The findings show that Hawu contains four phonemic implosive consonants (/?, ?, ?, ?/) that contrast with voiced stops and a six-vowel system that includes the mid-central vowel /?/. Although the three orthographic traditions represent most phonemes similarly, they differ substantially in their treatment of implosives and schwa. The UBB orthography consistently distinguishes these phonological contrasts, the LAI orthography preserves them through digraphs and additional orthographic conventions, whereas the Paddi orthography does not consistently differentiate implosives from voiced stops and represents schwa through less direct conventions. Based on the transparency criteria adopted in this study, the UBB orthography demonstrates the highest degree of orthographic transparency. The findings suggest that systematic phoneme–grapheme correspondences may facilitate literacy development while supporting language documentation and maintenance. Nevertheless, orthographic planning should balance linguistic evidence with community preferences, historical usage, institutional practices, and educational feasibility. Because the study is based on qualitative orthographic analysis and participant observations rather than experimental assessment of reading performance, the findings should be interpreted as identifying potential implications for literacy rather than demonstrating causal effects.